Mu-opioid receptor and receptor tyrosine kinase crosstalk: Implications in mechanisms of opioid tolerance, reduced analgesia to neuropathic pain, dependence, and reward - Gamble, Mackenzie C.; Williams, Benjamin R.; Singh, Navsharan; Posa, Luca; Freyberg, Zachary; Logan, Ryan W.; Puig, Stephanie (Frontiers in Systems Neuroscience, 2022)
Despite the prevalence of opioid misuse, opioids remain the frontline treatment regimen for severe pain. With continued use, opioid safety is dramatically reduced because of side-effects such as tolerance, resistance to neuropathic pain, physical dependence, or reward, promoting development of opioid use disorders and overdose deaths. Challenges in opioid research are related to the fact that signaling mechanisms downstream of the µ-opioid receptor (MOR) are purportedly intertwined to signaling mediating side-effects. One important challenge in opioid research is to uncouple cellular and molecular mechanisms that selectively modulate analgesia from those that mediate side-effects. One such mechanism could be the transactivation of receptor tyrosine kinases (RTKs) via the µ-opioid receptor (MOR), the primary target of prescription opioids. Notably, MOR-mediated side-effects can be uncoupled from analgesia signaling via targeting RTK family receptors, highlighting physiological relevance of MOR-RTKs crosstalk. This review focuses on the current state of knowledge surrounding the basic pharmacology of RTKs and bidirectional regulation of MOR signaling, as well as how MOR-RTK signaling may modulate undesirable opioid-related behaviors, including opioid tolerance, opioid resistance to neuropathic pain, physical dependence, and reward. Further research is needed to better understand RTK-MOR transactivation signaling pathways, and to determine if RTKs are a plausible therapeutic target for mitigating opioid side effects.